Dichloroacetate Decreases Cell Health and Activates Oxidative Stress Defense Pathways in Rat Alveolar Type II Pneumocytes. (2nd August 2015) - Valauri-Orton, Alexis; Bschorer, Frizzi; Bernd, Karen K.
Abstract : Dichloroacetate (DCA) is a water purification byproduct that is known to be hepatotoxic and hepatocarcinogenic and to induce peripheral neuropathy and damage macrophages. This study characterizes the effects of the haloacetate on lung cells by exposing rat alveolar type II (L2) cells to 0–24 mM DCA for 6–24 hours. Increasing DCA concentration and the combination of increasing DCA concentration plus longer exposures decrease measures of cellular health. Length of exposure has no effect on oxidative stress biomarkers, glutathione, SOD, or CAT. Increasing DCA concentration alone does not affect total glutathione or its redox ratio but does increase activity in the SOD/CAT oxidative stress defense pathway. These data suggest that alveolar type II cells rely on SOD and CAT more than glutathione to combat DCA-induced stress.